Analysis of Criminal Cases in Adamawa State, Nigeria - A, Akinrefon A.; I, Adeniyi O.; O, Adejumo A.; O, Olawale A.; A, Ubong B. (Global Journal of Social Sciences Studies, 2016)
The Occurrence of Criminal act worldwide is on the increase, curbing the menace of Crime effect to humanity has been a thing of concern, Adamawa state-Nigeria not excluded. The results show that Crime rate is on the increase and that the Age group that most involved in criminal act is between the Ages 16 – 35. Crime incidence in the state varies over the years given the age-group (i.e. Crime depends on year of occurrence, so also the criminals’ age group). Further analysis show that the all possible two-way interactions between crime, year of occurrence and gender (CY.CG.YG) in the first case is most appropriate for assessing crime cases in the state since it has the least AIC value for the first analysis while the model of association between crime cases and age-group independent of gender (CA.G) has the least AIC, and thus, is accepted to be the best model.